2021
DOI: 10.1002/srin.202100132
|View full text |Cite
|
Sign up to set email alerts
|

The Laboratory Study of Metallurgical Slags and the Reality

Abstract: The development of new materials and their production processes along with the environmental constraints demand new data of high quality, especially thermodynamic and physical property data. As slags play a crucial role in metallurgical processes and recycling, the need of better understanding of the reaction mechanisms between slag and metal is also increasingly felt. High precision data and better understanding of the reaction mechanism require efficient collaboration between the researchers in the laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 141 publications
(153 reference statements)
0
1
0
1
Order By: Relevance
“…While a nonarbitrary determination of the interfacial tensions can be made, in theory, the necessary condition for carrying out the measurements is the equilibrium state as any chemical reaction will influence the energy balance. [ 21 ] However, in this study, the effect of ongoing reactions is significant as the penetration is influenced by the amount of residual oxides, i.e., the reduction degree. Specifically, with ongoing reactions, it means the dissolution of the residual oxides by the penetrating slag.…”
Section: Discussionmentioning
confidence: 92%
“…While a nonarbitrary determination of the interfacial tensions can be made, in theory, the necessary condition for carrying out the measurements is the equilibrium state as any chemical reaction will influence the energy balance. [ 21 ] However, in this study, the effect of ongoing reactions is significant as the penetration is influenced by the amount of residual oxides, i.e., the reduction degree. Specifically, with ongoing reactions, it means the dissolution of the residual oxides by the penetrating slag.…”
Section: Discussionmentioning
confidence: 92%
“…Uloga troske je višestruka, a najvažnija je da asimilira neželjene primjese. 17 Tijekom oksidacije željeza i primjesa nastali oksidi prelaze u trosku koja može biti i koristan sporedni proizvod. [18][19][20][21][22][23] Troska nastaje i od drugih dodataka uloženih u proizvodne agregate (npr.…”
Section: Uvodunclassified
“…In contrast, recent reviews on high-temperature slag viscosity studies concluded that these rheology parameters are often not reported 9 and thereby the reported values do not accurately represent the viscosity of this high-temperature suspension. 10 There are two main causes for the lack of reporting and controlling: first, there is a lack of emphasis on the complexity and the wide-variety of parameters which control the rheology of high-temperature suspensions. 10 Second, the crystals inside a slag are non-inert and precipitate, grow or dissolve depending on the temperature or composition.…”
Section: Introductionmentioning
confidence: 99%
“…10 There are two main causes for the lack of reporting and controlling: first, there is a lack of emphasis on the complexity and the wide-variety of parameters which control the rheology of high-temperature suspensions. 10 Second, the crystals inside a slag are non-inert and precipitate, grow or dissolve depending on the temperature or composition. Therefore, the shape, size and volume fraction of the crystals within a slag can vary with the thermal history of the slag or changes in composition, however, hightemperature viscosity measurements devices are commonly not equipped with the possibility to measure the particle morphology at the temperature of interest.…”
Section: Introductionmentioning
confidence: 99%